Tumor-Associated Macrophages in Tumor Immunity - Pan, Yueyun; Yu, Yinda; Wang, Xiaojian; Zhang, Ting (Frontiers in Immunology, 2020)
Tumor-associated macrophages (TAMs) represent one of the main tumor-infiltrating immune cell types and are generally categorized into either of two functionally contrasting subtypes, namely classical activated M1 macrophages and alternatively activated M2 macrophages. The former typically exerts anti-tumor functions, including directly mediate cytotoxicity and antibody-dependent cell-mediated cytotoxicity (ADCC) to kill tumor cells; the latter can promote the occurrence and metastasis of tumor cells, inhibit T cell-mediated anti-tumor immune response, promote tumor angiogenesis, and lead to tumor progression. Both M1 and M2 macrophages have high degree of plasticity and thus can be converted into each other upon tumor microenvironment changes or therapeutic interventions. As the relationship between TAMs and malignant tumors becoming clearer, TAMs have become a promising target for developing new cancer treatment. In this review, we summarize the origin and types of TAMs, TAMs interaction with tumors and tumor microenvironment, and up-to-date treatment strategies targeting TAMs.